EVALUATION OF AWARENESS AND READINESS TO INVEST IN HPV VACCINE AMONG WOMEN WITH DOCUMENTED HIV STATUS IN OYO STATE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This study investigated the level of awareness and financial preparedness of women with confirmed HIV status in Oyo State regarding the HPV vaccine. The results indicated a limited inclination among these women to invest in HPV vaccines in the surveyed region. The Health Promotion Model served as the framework for the study, utilizing a descriptive cross-sectional research approach. A multi-stage sampling method was employed to select 397 women living with HIV in the study area, and data were collected through a pretested self-structured questionnaire. The collected data were coded and entered into SPSS version 23.0 for analysis, employing both descriptive and inferential statistical techniques with significance levels set at p≤0.05.The mean age of the respondents was 44.18 ± 9.54 years, with 45.1% having secondary education as their highest educational qualifications. Knowledge levels were observed, with 15.9% and 53.4% having good knowledge of HPV and cervical cancer, respectively. Only 17.1% demonstrated good knowledge of the HPV vaccine, while 16.1% expressed a willingness to pay for it. Additionally, 58.9% were willing to have their daughters vaccinated, and 55.4% acknowledged a willingness to cover the cost of their daughters' vaccine. Education status was found to be significantly associated with women's knowledge of HPV (p